Estimating crop-specific production technologies in Chinese agriculture: a generalized maximum entropy approach - Zhang, Xiaobo; Fan, Shenggen (International Food Policy Research Institute, 1999)
A Generalized Maximum Entropy (GME) approach is adapted to empirically estimate crop-specific production technologies in Chinese agriculture. Despite a modest behavior assumption about equal marginal returns of non-land inputs among crops, this method does not require price information, which is usually distorted in a centrally planned economy such as China. Multi-output technologies for seven regions over more than two decades are estimated, and input allocations for each province are recovered simultaneously. The estimated multi-output production technology and input allocations imply that China may have greater grain production potentials than previously thought.